Psychological Distress and Coping Adaptation Among Relatives of Critically Ill Adults in an Intensive Care Unit: A Cross-Sectional Correlational Study - Maria Sasdim Yati; Vivin Nur Hafifah; Setiyo Adi Nugroho (Adult Health Nursing Journal, 2026)
Background: Relatives of critically ill adults may experience considerable psychological distress during intensive care hospitalisation due to uncertainty, restricted contact, complex clinical information, and fear of patient deterioration. The way families adapt to this situation is reflected in their coping responses, which may be adaptive or maladaptive depending on emotional, informational, and social resources available during critical care.Objective: This study aimed to analyse the association between family psychological stress and coping adaptation among relatives of critically ill patients in an adult intensive care unit. Methods: A cross-sectional correlational study was conducted among 130 relatives of critically ill patients admitted to the Intensive Care Unit of RSU Dr. H. Koesnadi Bondowoso, Indonesia. Respondents were recruited using quota sampling based on predetermined eligibility criteria. Family stress was assessed using an observational checklist, while coping adaptation was measured using a structured coping questionnaire. Data were analysed using descriptive statistics and Spearman’s rho correlation test, with statistical significance set at p < 0.05.Results: Most respondents experienced stress level IV, involving 78 participants (60.0%), followed by stress level V in 35 participants (26.9%) and stress level III in 17 participants (13.1%). Maladaptive coping was identified in 91 respondents (70.0%), while 39 respondents (30.0%) demonstrated adaptive coping. Spearman’s rho analysis showed a significant association between family stress level and coping adaptation (r = 0.354; p < 0.001).Conclusion:  Family psychological stress was significantly associated with coping adaptation among relatives of critically ill patients in the ICU. The findings indicate that families experiencing psychological strain may require early assessment, clear communication, and supportive nursing approaches to strengthen adaptive coping during critical care hospitalisation.